On the Feasibility of Verification of 3D Dosimetry Near Brachytherapy Sources Using PRESAGE/Optical-CT - Pierquet, M (2010)
PURPOSE: The feasibility of using the PRESAGE/Optical-CT system for 3D dosimetry verification around a brachytherapy source is investigated. METHOD AND MATERIALS: Brachytherapy dose distributions were obtained by irradiation of cylindrical PRESAGE volumes 6cm in diameter by 8cm height with a GammaMed 12i Ir-192 HDR unit (Varian Medical Systems). A narrow channel on the central axis was created by setting a steel catheter in the Presage during manufacture, enabling measurements close to the source (~3mm). RESULTS: Comparison of dose line profiles shows good agreement between PRESAGE and verified calculated dose calculation, in both high and low dose regions. CONCLUSION: The PRESAGE/Optical-CT shows good potential in verification of 3D dose distributions around brachytherapy sources.